Research and statistics a practical introduction to nurses - Hicks, Carolyn M (Prentice Hall, 1990)
"Research and Statistics: A Practical Introduction for Nurses" explains the essential concepts and procedures of research design and analysis, to enable the nurse researcher to gain a reasonable knowledge-base from which to begin a research project.